Mucormycosis Rhinosinusitis at Diagnosis of Acute Lymphoblastic Leukemia. Issue 3 (April 2015) - Mandegari, Elham; Fu, Ligia; Arambú, Carolina; Montoya, Sandra; Peña, Armando; Johnson, Kyle M.; Perfect, John R.; Caniza, Miguela A.
<x xml:space="preserve">Abstract</x> We present the case of an adolescent with mucor rhinosinusitis diagnosed concomitantly with acute lymphoblastic leukemia at a hospital in Tegucigalpa, Honduras. We also discuss the challenges faced in the dual management of hematologic malignancies and invasive fungal disease in a low–middle-income country, such as access to diagnostics, immunosuppressants, imaging, and antifungals. Despite these shortcomings, the patient was successfully treated for both the diseases. Low–middle-income country hospitals can effectively treat invasive fungal diseases by providing adequate diagnostic and support services, which can improve the outcomes of pediatric cancer patients.